2019
DOI: 10.1186/s12950-019-0232-0
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor inhibits TLR3-induced inflammatory cascades in human corneal epithelial cells

Abstract: BackgroundIn herpes simplex epithelial keratitis, excessive TLR3-induced cellular responses after virus infection evoke inflammatory cascades that might be destructive to the host cornea. Nerve growth factor (NGF), a pluripotent neurotrophic factor with immune regulatory effect, was proved to be effective in Herpes simplex keratitis (HSK) treatment, although the detailed mechanisms remain unclear. This study aims to investigate the effects of NGF on modulating inflammatory responses triggered by TLR3 activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…NGF binds to its receptor TrkA and drives neuron survival and neurite outgrowth via PI3K/Akt and Ras/MAPK signaling, respectively. Investigations by other groups also demonstrated that NGF could dampen in ammatory response via downregulating proin ammatory cytokines including TNFα [48,49] Our study found that NGF inhibited TNFα expression and such inhibitory effect was abolished by NGF neutralizing antibody or TrkA inhibitor. These results imply that NGF secreted by BMSCs inhibited TNFα/RelB pathway and induced remyelination, in consistence with the results of other groups [48,50].…”
Section: Discussionsupporting
confidence: 70%
“…NGF binds to its receptor TrkA and drives neuron survival and neurite outgrowth via PI3K/Akt and Ras/MAPK signaling, respectively. Investigations by other groups also demonstrated that NGF could dampen in ammatory response via downregulating proin ammatory cytokines including TNFα [48,49] Our study found that NGF inhibited TNFα expression and such inhibitory effect was abolished by NGF neutralizing antibody or TrkA inhibitor. These results imply that NGF secreted by BMSCs inhibited TNFα/RelB pathway and induced remyelination, in consistence with the results of other groups [48,50].…”
Section: Discussionsupporting
confidence: 70%
“…NGF binds to its receptor TrkA and drives neuron survival and neurite outgrowth via PI3K/Akt and Ras/MAPK signaling, respectively. Investigations by other groups also demonstrated that NGF could dampen inflammatory response via downregulating proinflammatory cytokines including TNFα [ 56 , 57 ]. Our study found that NGF inhibited TNFα expression and such inhibitory effect was abolished by NGF neutralizing antibody or TrkA inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Reins et al [ 35 ] have shown that in epithelial cells, 1,25(OH) 2 VD 3 inhibited poly(I:C)-induced IL-1β secretion. Because ROS production is involved in poly(I:C)-proinflammatory action [ 36 ], NRF2-HO-1 axis activation by 1,25(OH) 2 VD 3 partly explain why 1,25(OH) 2 VD 3 inhibits poly(I:C)-induced IL-1β secretion in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%